Sociocarbon cycles: Assembling and governing forest carbon in Indonesia. Issue 99 (February 2019) - McGregor, Andrew; Challies, Edward; Thomas, Amanda; Astuti, Rini; Howson, Peter; Afiff, Suraya; Kindon, Sara; Bond, Sophie
Graphical abstract: Highlights: Sociocarbon cycles highlight the relations that comprise forest carbon governance. REDD+ is creating new relations between C atoms, technology and institutions. More just carbon governance is possible through sociocarbon analysis. Abstract: As Indonesia's REDD+ (Reducing Emissions from Deforestation and forest Degradation) program unfolds, it is transforming people and places in unexpected ways, and reconfiguring human and non-human processes. In this paper we recognize that forest carbon governance is about much more than carbon. Reflecting on observations from research in Indonesia, we develop the concept of sociocarbon cycles in an effort to move beyond the human-nature dualisms that characterize much work on REDD+. We see carbon governance as emergent sets of arrangements that are continually tested and challenged through the agency of diverse human and non-human actors. Drawing on insights from the literature on socionatures, and in particular on work on hydrosocial cycles, we approach carbon as a socionatural achievement, constituted through relations among institutions, carbon technologies, and C atoms. Our approach recasts REDD+ as an inherently political program, rather than a techno-scientific response to climate change. This, we contend, opens up new ways of conceptualizing and approaching carbon. A sociocarbon lens highlights the importance of social research in reconceptualising biophysical carbon cycles; brings questions of justice and power to the fore (who wins and who loses from carbon initiatives); and aids in understanding what carbon is, how it is made known, and how competing carbon claims are sustained. We suggest that a sociocarbon lens provides multiple points of entry to pursue more just geometries of power.